The role of culturally appropriate interpersonal communication strategies to reduce hepatitis B and liver cancer disparities - Zovich, Beatrice; Block, Suzanne J.; Borondy-Jenkins, Fiona; Moraras, Kate; Chen, Thomas; Adedokun, Rukayat; Hua, Dung; Cohen, Chari (Frontiers in Public Health, 2024)
Introduction Asian and Pacific Islander (API), African, and Caribbean immigrant groups in the U.S. are disproportionately impacted by chronic hepatitis B and hepatocellular carcinoma (primary liver cancer). Creating educational communication campaigns about hepatitis B and liver cancer for these communities is necessary to increase disease-related awareness and prompt health-promoting behaviors. Identifying interpersonal communication (IPC) preferences within diverse communities for integration into an educational campaign that emphasizes the link between hepatitis B and liver cancer can ultimately promote uptake of screening, vaccination and linkage to appropriate care. Methods Fifteen focus groups and two key informant interviews were conducted with participants from Micronesian, Chinese, Hmong, Nigerian, Ghanaian, Vietnamese, Korean, Somali, Ethiopian, Filipino, Haitian, and Francophone West African communities. Data were analyzed using thematic coding and analysis. Results Findings demonstrate that all communities preferred that materials be offered in both English and native languages and emphasized that campaigns highlight the connection between hepatitis B and liver cancer. Educational sessions should take place in settings where communities feel safe, including community-based organizations, religious establishments, and healthcare offices, and should be facilitated by trusted messengers, including patient navigators, doctors and faith leaders. Presenting accurate information and dispelling myths and misconceptions around hepatitis B, liver cancer, and their connection were the biggest needs identified across all focus groups. Discussion This study provides insight into community-specific preferences for learning about hepatitis B and liver cancer through IPC methods. The findings from this study can be used to design multi-platform, culturally and linguistically appropriate health education campaigns to facilitate improved diagnosis, prevention, and management of hepatitis B and liver cancer among heavily impacted communities in the U.S.